PTU-154 HMGB1 As a Prognostic Biomarker in The Progression of Barrett's Oesophagus. (17th August 2016) - Porter, R; Murray, R; , GI; Petty, R; El-Omar, EM; Hold, GL; McLean, MH
Abstract : Introduction: Barrett's oesophagus (BO) is metaplasia from normal squamous to mucin secreting columnar epithelium. BO is a precursor of neoplastic progression to dysplasia and adenocarcinoma, with no associated progression biomarker available. High Mobility Group Box-1 (HMGB1) is a ubiquitous nuclear protein that regulates gene expression. When phosphorylated, it translocates to the cytoplasm and extracellular space to stimulate pro-inflammatory responses and influence epithelial cell behaviour. Our aim was to assess expression of HMGB1 in BO and neoplastic progression. Methods: Epithelial nuclear and cytoplasmic subcellular expression of HMGB1 was assessed immunohistochemically in endoscopically retrieved paraffin embedded biopsies sourced from the Grampian Biorepository (n = 155 total). Ethical approval was granted by the Grampian biorepository scientific committee. A gastrointestinal pathologist (GIM) confirmed histological diagnosis. 18, 25, 78 and 13 biopsies were assessed, from 11 patients with normal oesophageal mucosa, 14 patients with normal gastric mucosa, 20 patients with non-dysplastic BO and 9 patients with dysplastic BO, respectively. Also included were 12 biopsies (7 patients) and 9 biopsies (6 patients) from non-dysplastic BO associated with progression to dysplasia and adenocarcinoma, respectively. Intensity of HMGB1 staining was double scored as none, weak, moderate or strong immunopositivity. Analysis used Fisher's exact test of 2X2 contingency tables. Results: HMGB1 was expressed in the nuclei in all groups. Normal oesophageal biopsies expressed no or weak cytoplasmic HMGB1. Non-dysplastic (p < 0.0001) and dysplastic (p < 0.0001) BO epithelium expressed stronger cytoplasmic HMGB1 compared to both normal oesophageal and gastric epithelium. Dysplastic BO expressed increased HMGB1 in both nuclear (p = 0.0003) and cytoplasmic (p = 0.0002) compartments compared to non-dysplastic BO. Background non-dysplastic BO in those that had progressed to dysplasia had increased nuclear HMGB1 compared to non progressors (p = 0.015). Background non-dysplastic BO in those who progressed to cancer expressed less cytoplasmic HMGB1 compared to non progressors (p = 0.0118). Non-dysplastic and dysplastic BO epithelium had clear foci of absent nuclear HMGB1 expression in areas of moderate/strong cytoplasmic HMGB1 expression. Conclusion: There was evidence of dynamic subcellular localisation of HMGB1 expression in association with BO and dysplasia. Cytoplasmic HMGB1 expression may be a novel biomarker to aid diagnosis and predict progression of BO. The functional significance of this warrants further investigation. Disclosure of Interest: None Declared